Handling Regional Boundary Conflicts Between Mamasa Regency and Polewali Mamasa Regency in West Sulawesi Province - An Nisa Atila Thabrani; Malik, Ichsan; Halomoan Freddy Sitinjak; wilopo, Wilopo; Prihatin, Endang (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The problem of conflict in the Mamasa Regency and Polewali Mamasa Regency areas is due to differences of opinion regarding Law (UU) Number 11 of 2002 concerning the expansion of the Polmas Regency into Mamasa Regency and Polmas Regency. He explained that his party would follow up on Law Number 11 of 2002 which stated that three sub-districts, namely Aralle, Tabulahan, Mambie (ATM) were part of Mamasa Regency. However, some Polmas residents still adhere to the decision of the DPRD Polmas which gives freedom to residents who do not want to join Mamasa to join Polmas. This research use desciptive qualitative approach. The research location is located on the border of Mamasa Regency and Polewali Mamasa Regency. Data collection was carried out through library research. The research results show that the regional boundary conflicts that arise are more due to Law Number 11 of 2002 not considering the interests of parties who do not want to join Mamasa Regency, so they are forced to; repaired. Looking at the practical reality, several causes of conflict related to territorial boundaries have been identified, namely legal, economic, cultural, political and demographic, social and administrative factors. The step taken was to revise Law Number 11 of 2002 concerning the expansion of Community Policing into Mamasa Regency and Polres which was assisted by the West Sulawesi Provincial Government by involving Muspida and the Ministry of Home Affairs. With this process, both regions agree to accept the results of each decision prepared by the regional government and central government, taking into account the objections and wishes of each region.